Respuesta :
Answer:
option C.
Step-by-step explanation:
we have
System A
[tex]6x+y=2[/tex] ---> first equation system A
[tex]-x-y=-3[/tex] ----> second equation system A
Multiply the second equation by 4 both sides
[tex]4(-x-y)=4(-3)[/tex]
[tex]-4x-4y=-12[/tex]
Adds this equation to the first equation system A
[tex]-4x-4y=-12\\6x+y=2\\-----\\-4x+6x-4y+y=-12+2[/tex]
[tex]2x-3y=-10[/tex] ----> first equation system B
[tex]-x-y=-3[/tex] ----> second equation system B
so
The first equation of System B is obtained by adding the first equation of System A to 4 times the second equation of System A
The second equations are identical
therefore
They will have the same solution